Pengaruh Terapi Reminiscence Terhadap Harga Diri Lansia di UPTD Pelayanan Sosial Lanjut Usia Tresna Werdha Natar - Madepan Mulia; Rina Mariani; Deni Metri (Jurnal Ners, 2023)
The number of elderly tends to increase every year. An increase in the number of elderly is also usually followed by physical, mental, spiritual, economic and social changes. The aging process has an impact on a decrease in physical, mental, psychosocial conditions, changes related to work and the social role of the elderly. Problems in the elderly can cause stress which is characterized by feelings of uselessness, not needed and feelings of being left out. This situation has the potential to cause problems in the elderly, one of which is low self-esteem. The aim of the study was to determine the effect of reminiscence therapy on the self-esteem of the elderly at the UPTD Tresna Werdha Natar Elderly Social Services. This study used a quantitative method with a quasi-experimental design with a pre-post test without a control group using a purposive sampling technique and a random sampling method with a total sample of 30 respondents. The samples taken were the elderly who experienced low self-esteem with a score <15. The researcher used the Rosenberg Self Esteem Scale (RSES) questionnaire to measure the self-esteem of the elderly. The results showed that after being given reminiscence therapy in the elderly there was an increase in self-esteem. Nurses are expected to be able to provide reminiscence therapy to the elderly who experience low self-esteem.